2020
DOI: 10.21203/rs.2.22425/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regional heterogeneities of health literacy in China: a population-based study

Abstract: Background: Few studies described the geographic variations of health literacy in China. This study aimed to investigate the regional heterogeneities of health literacy level in Chinese population, in order to formulate targeted health literacy promotion strategies in different economic and cultural contexts.Methods: Multi-stage stratification, clustering, and random sampling methods were used to select 70 study sites from 25 provinces or municipalities in China. Health literacy was measured using the National… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…e secondary industry covers health food processing and manufacturing, pharmaceutical manufacturing, health equipment manufacturing, and other industries. e tertiary industry covers medical and health services, wholesale and retail of health products, public facilities management, health management, health financial services, and other industries, as well as public welfare undertakings that provide a good ecological environment, healthcare combined with healthcare services, and ecological leisure tourism [5,6]. From this point of view, the health industry has the dual attributes of people's livelihood and science and technology.…”
Section: Introductionmentioning
confidence: 99%
“…e secondary industry covers health food processing and manufacturing, pharmaceutical manufacturing, health equipment manufacturing, and other industries. e tertiary industry covers medical and health services, wholesale and retail of health products, public facilities management, health management, health financial services, and other industries, as well as public welfare undertakings that provide a good ecological environment, healthcare combined with healthcare services, and ecological leisure tourism [5,6]. From this point of view, the health industry has the dual attributes of people's livelihood and science and technology.…”
Section: Introductionmentioning
confidence: 99%
“…The mean score (34.19, SD = 6.18) of health literacy represented a limited health literacy of the sample (Chinese Ministry of Health 2009), which supported a previous finding that the basic health literacy among Chinese residents was limited from low to moderate. 22,34,35 Previous research revealed that older patients were associated with lower health literacy, 36 and age was identified as a factor that need to be considered when reading comprehension was required for certain health or medical tasks. However, this trend was not observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Turkey reported that 30.9% of the participants had inadequate HL levels and 38.0% had problematic/limited HL levels (Özkan et al, 2018). That study's results showed that age, education, income, employment, and health knowledge had some impact on HL levels (Li et al, 2021; Okan et al, 2019; Özkan et al, 2018; Rajah et al, 2019). Low HL among older adults is associated with increased reports of poor physical functioning, pain, limitations in daily activities, and poor mental health status (Wolf et al, 2005, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This concept is seen as an integral part of individual HL and its results include the ability to understand the community's public health messages as well as participate in and evaluate the civil movement on health care issues (Ad Hoc Committee on Health Literacy for the Council on Scientific Affairs, American Medical Association, 1999). Low HL is still a public health problem in Turkey as it is in other nations (Li et al, 2021; Okan et al, 2019; Rajah et al, 2019). A study conducted in Turkey reported that 30.9% of the participants had inadequate HL levels and 38.0% had problematic/limited HL levels (Özkan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%